The Existence of Kayaq Sandongan Art in Enriching the Civic Culture of the Sasak Community - Mayasari, Dian Eka; Ilmiawan, Ilmiawan; Masyitah, Putri Maya; Sarah, Fidlia Mae (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This research generally aims to: a) describe the efforts of the Sasak people in maintaining the existence of the Kayaq Sandongan art; b) the values contained in the Kayaq Sandongan art as the civic culture of the Sasak people. This research is a descriptive study with a qualitative approach. The research object is the values of character education and the meaning of character education values in Kayaq Sandongan. Data was collected by determining the units and recording then analyzed by data reduction and data analysis. Inference based on four categories of educational character values. Semantic validity and expert interviews were used to validate the research results. Based on the results of the study, it can be concluded that the existence of Kayaq Sandongan is maintained because there is a community that supports the Kayaq Sandongan art, artists who have passed it down from generation to generation and support for the village and district governments. There are four values of character education in the Kayaq Sandongan mask dance, namely: 1) religious values, 2) values of responsibility and hard work, 3) values of tolerance, and 4) values of caring for the environment.